Gas Emmision Testing of Fuel Based Vehicles at Banda Aceh, Indonesia - Intan Mulia Sari; Juli Erlia; Desy Fitriana; Elin Yusibani (Journal of Aceh Physics Society, 2015)
A gas emmision decent testing of vehicles based on fuel has been done by EIA (Environmental Impact and Analysis). It is important to do the testing to determine the vehicles meet the technical requirements and road-worthy. The results showed that for 1.572 vehicles which is performing emissions testing have obtained 11% that could be potentially pollute the air on vehicles that using gasoline, and 42% on vehicles that using diesel. Based on the total number of four-wheeled vehicles that performed emissions testing in the city of Banda Aceh showed that 82% environmentally friendly vehicles and 18% potentially pollute the air.